Changes in social security eligibility and the international mobility of New Zealand citizens in Australia - Jacques Poot; Lynda Sanderson (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
This paper is concerned with the international mobility of New Zealanders who migrate to Australia. One in ten New Zealand citizens lives in Australia and their settlement and subsequent mobility is important from demographic, socio-economic and policy perspectives in both countries. Using a unique longitudinal dataset on New Zealand citizens arriving for a stay of 12 months or longer between 1 August 1999 and 31 July 2002, we track all subsequent moves of these migrants out of and back into Australia, up to July 2005. This allows us to assess the impact of the removal of labour market-related social security eligibility and some other policy changes affecting New Zealand migrants to Australia, implemented between February and June 2001. United Kingdom migrants to Australia, who were not affected by the policy changes, provide a "control group". Using hazard models, we find that the policy changes increased the probability of remigration from Australia among those who had intended to settle permanently. Competing risk models suggested no difference between the impact of the policy changes on onward or return moves. Settlers arriving after the policy changes spend less time Australia and make more trips away than earlier migrants.
Keywords: C41; F22; J61; 330; International Migration; International Travel; New Zealand; Australia; United Kingdom; Social Welfare; Immigration Policy; Selectivity